Current Status of Social Responsibility For Mongolian Mining Companies - Zanabazar, Altanchimeg; Battuya, B. (Jurnal Ilmiah Peuradeun, 2019)
The social responsibility of mining companies is not only the for the certain companies but also raises concern in the socioeconomic level of the country. While there is currently no legal regulation on corporate social responsibility in our country, companies are still implementing it voluntarily. The survey results show that the major mining companies are paying more attention to social responsibility reflecting in their strategic plans. Based on corporate social responsibility reports of 85 mining companies, we have reviewed the current situation of CSR.